The Effect of Clinical Supervision on the Pedagogic Competence of Vocational School Teachers - Sari, Emilia; Masduki, Ahmad; Matin, Matin (Journal of Education Research and Evaluation, 2021)
The purpose of this study was to obtain information about the effect of clinical supervision and self-efficacy on teacher pedagogic competence. The place of research is at State Vocational High Schools in West Jakarta Administration City. This study used a survey method with path analysis techniques and a causal quantitative approach. The sample in this study was 72 teachers who were taken using simple random sampling technique or simple random sampling and the teacher who became the object of the research was determined using the sample technique formula from Slovin. The data were analyzed using descriptive and inferential statistics by first doing the prerequisite analysis test, namely population normality and regression analysis. The findings from the study show that the success of school principals in the clinical supervision process will determine teacher pedagogical competence. Competent teachers can manage to learn well and increase student learning motivation so that learning objectives are achieved and produce students who excel in their fields. This can be achieved if the implementation of clinical supervision is carried out in the right and proper way.